Endovascular embolisation in acute arterial haemorrhage cases and hypervascular lesions: a single institution experience - Md Ralib @ Md Raghib, Ahmad Razali; Nik Yusoff, Nik Rizal; Abdul Rashid, Mohd Amran (2011)
Introduction Endovascular embolisation had played a major role in the acute management of acute arterial haemorrhage. It had proven benefits in acute upper and lower gastrointestinal haemorrhage, massive haemoptysis, bleeding visceral pseudoaneurysms and arteriovenous malformations. It also had played a major role in the preoperative embolisation of hypervascular lesions such as paraganglioma, meningioma, juvenile angiofibroma and other hypervascular lesions, with proven reduction in blood loss intraoperatively.